Viral Hepatitis in India - Suresh Kishanrao (Archives of Hepatitis Research - Peertechz Publications, 2020)
Viral hepatitis is a cause for major health care burden in India and is recently equated as a threat comparable to the "big three" communicable diseases - HIV/AIDS, Malaria, and Tuberculosis. Hepatitis A virus and Hepatitis E virus are predominantly enterically transmitted pathogens and are responsible to cause both sporadic infections and epidemics of acute viral hepatitis. Hepatitis B virus and Hepatitis C virus are predominantly spread via parenteral route and are notorious to cause chronic hepatitis which can lead to grave complications including cirrhosis of liver and hepatocellular carcinoma.  The Government of India launched a new National Viral Hepatitis Control Program (NVHCP) on World Hepatitis Day -28 July 2018. It will be an integrated approach for prevention and control of viral hepatitis, with a view to provide free of charge screening, diagnosis, treatment & counselling services to all, and specially to people belonging to high-risk groups to achieve SDG goal 3.3 which aims ending viral hepatitis by 2030 as envisaged in National Health Policy 2017. This review article aims to cover the basic virologic aspects of these viruses and highlight the present scenario of viral hepatitis in India, justifying the launch of National Viral Hepatitis Control Program.